2021
DOI: 10.3389/fnbeh.2021.749517
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Conditioning With Simultaneous and Backward Conditioned Stimulus: Implications for Models of Pavlovian Conditioning

Abstract: In a new environment, humans and animals can detect and learn that cues predict meaningful outcomes, and use this information to adapt their responses. This process is termed Pavlovian conditioning. Pavlovian conditioning is also observed for stimuli that predict outcome-associated cues; a second type of conditioning is termed higher-order Pavlovian conditioning. In this review, we will focus on higher-order conditioning studies with simultaneous and backward conditioned stimuli. We will examine how the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Temporal difference learning, a reward prediction error-based learning model that relates to the integrator model (Bush & Mosteller, 1951) and the Rescorla-Wagner learning model (Rescorla & Wagner, 1972), accounts for SOC. However, it fails to explain SPC as the CS1 has no predictive value during Phase 1 of SPC, while it does in Phase 2 of SOC (for a review, see Prével & Krebs, 2021). The structure and timing of integration in higher order conditioning is still a matter of debate (for a review, see Holmes, Wong, et al, 2022).…”
Section: Dacr Beyond Cs-us Conditioningmentioning
confidence: 99%
“…Temporal difference learning, a reward prediction error-based learning model that relates to the integrator model (Bush & Mosteller, 1951) and the Rescorla-Wagner learning model (Rescorla & Wagner, 1972), accounts for SOC. However, it fails to explain SPC as the CS1 has no predictive value during Phase 1 of SPC, while it does in Phase 2 of SOC (for a review, see Prével & Krebs, 2021). The structure and timing of integration in higher order conditioning is still a matter of debate (for a review, see Holmes, Wong, et al, 2022).…”
Section: Dacr Beyond Cs-us Conditioningmentioning
confidence: 99%
“…Can auto-conditioning thus happen at all? Several studies have found that a CS can gain excitatory value even if it starts after the US, be it in a simultaneous or even backward conditioning configuration (e.g., Barnet et al 31 ; Cole and Miller 32 ; Prével et al 33 ), although the boundary conditions for simultaneous or backward conditioning to occur are likely more constrained compared to forward conditioning. For a long time, this seemed at odds with the basic tenets of learning theory, that stimuli need to be predictive to trigger learning (for an overview, see Chang et al 34 ).…”
Section: Introductionmentioning
confidence: 99%